Development and Standardization of Scale to Measure Farmer’s Attitude towards Farmers’ Producer Company - Mukherjee, Anirban; Singh, Premlata; Satyapriya; Rakshit, Shantanu; Burman, Rajarshi Roy (Indian Journal of Extension Education, 2018)
Attitude plays a crucial role in influencing one’s behaviour with respect to a particular psychological object. To measure the attitude of farmers towards newly formed Farmers’ Producer Company (FPC), need was realized to use a scale. But due to the non-availability of a proper scale for measuring the attitude of farmers towards Producer Company, a Likert’s Summated Rating scale was constructed by following the methodology suggested by Likert (1932) and Edward (1957). Attitude towards FPC was categorized in two specific dimensions (i) Performance, role and potential of FPC, and (ii) the organizational climate of FPC. A total 68 statement were constructed and was sent to 154 judges through email, google docs form and handed over personally. Based on the 61 judges response 34 statements were screened out for item analysis. The scale was administered to 64 farmers of Haryana, Bihar and West Bengal. The split half method was followed for testing reliability of the scale and reliability co-efficient was 0.65. The validity of the scale was examined with the help of face and content validity. The scale developed finally consists of 28 statements out of that 19 statements are positive and 9 statements are negative. The scale is reliable and can produce consistent results.
Keywords: Attitude; behaviour; farmers organization; likert’s summated rating scale; reliability; validity and standardized scale